Lupane Triterpene Derivatives Improve Antiproliferative Effect on Leukemia Cells through Apoptosis Induction - Lía S. Valencia-Chan; Neptis Estrada-Alfaro; Jimmy Josué Ceballos-Cruz; Luis W. Torres-Tapia; Sergio R. Peraza-Sánchez; Rosa E. Moo-Puc (Molecules, 2022)
Leukemia is one of the most frequent types of cancer. No effective treatment currently exists, driving a search for new compounds. Simple structural modifications were made to novel triterpenes isolated from Phoradendron wattii. Of the three resulting derivatives, 3α-methoxy-24-hydroxylup-20(29)-en-28-oic acid (T1m) caused a decrease in the median inhibitory concentration (IC50) on the K562 cell line. Its mode of action was apparently apoptosis, ROS generation, and loss of mitochondrial membrane potential (MMP). Molecular docking analysis showed T1m to produce lower binding energies than its precursor for the Bcl-2 and EGFR proteins. Small, simple, and viable modifications to triterpenes can improve their activity against leukemia cell lines. T1m is a potentially promising element for future research. Clarifying the targets in its mode of action will improve its applicability.